ACCOUNTING OF INNOVATIONS: ORGANIZATIONAL AND METHODOLOGICALASPECTS - KASHCHENA, Nataliia; NESTERENKO, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to improving the organizational and methodological principles of accounting for innovations in the management information system of an enterprise with an emphasis on income, expenses and results of innovation activities. The state of Ukraine's innovation ecosystem and its place in the global innovation ranking are identified. Based on the negative dynamics of the components of the global innovation index, problems in the integration of innovative approaches into the processes of creating added value are recognized. The necessity of significant modernization of information support of managerial influences on the innovative activities of business entities is proved, the expediency of a systematic approach to reforming accounting processes and creating a favorable environment for the development of innovative activities of enterprises is emphasized. The necessity of forming an accounting policy taking into account the specifics of innovation activity, in particular through the detailing of accounting accounts and digitalization of business processes, is substantiated. The author proposes an infological model of accounting policy that integrates financial, social and environmental aspects and facilitates the detailing of income, expenses and results of innovative activities of enterprises, ensuring transparency, accuracy and timeliness of data for making management decisions. The article presents a chart of accounts that provides for the allocation of second- and third-order subaccounts to detail information on costs, income and results of innovation activities for more accurate analysis and effective management of the company's financial flows. The possibilities of using ERP systems and tools of artificial intelligence, machine learning and Big Data to automate accounting processes, evaluate and monitor the effectiveness of innovations are considered. It is noted that the implementation of the proposed solutions contributes to the standardization and optimization of the presentation of data on income, costs and results of innovation in a convenient format, providing an integrated approach to the organization and implementation of accounting and analytical procedures.
Keywords: innovation; accounting; accounting policy; digitalization; innovative development; enterprise management